A Study on the Problem Faced by the Rural Cottage Workers in Villianur Commune Of Puducherry - Dr.T.Sezhiyan, Mr.D.Gnanadeiveegam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Before and after 1947 India have been making various and numerous polices in wide spectrum of social developments ,unfortunately it s not reveled and advertised to needy and concern people to get benefit herby interested people on doing particular business also becoming as disinterested on doing business therefore along with policy formulation they have to watch whether it is reaching and flowing toward correct place if so it would make sufficient and expected results in the concern fields .There are no much significant progress and developments in the several departments of Indian administration despite it had been enacted numerous law and polices. Enacted law and polices of government of India have to properly make reach to concern people developments by its officers thereby expected success, goal, progress and achievement could be achieved .They face multifarious problems in their dwelling places further they would like to succeed in their life beyond their hurdles with an interest to protect and make prosperous their civic life ,for which government have to initiate protective and motivating polices.